2012
DOI: 10.3390/md10102337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Administration of Fucoidan Extracted from Cladosiphon okamuranus on Tumor Growth and Survival Time in a Tumor-Bearing Mouse Model

Abstract: We evaluated the anti-tumor activities of the oral administration of fucoidan extracted from Cladosiphon okamuranus using a tumor (colon 26)-bearing mouse model. The materials used included low-molecular-weight fucoidan (LMWF: 6.5–40 kDa), intermediate-molecular-weight fucoidan (IMWF: 110–138 kDa) and high-molecular-weight fucoidan (HMWF: 300–330 kDa). The IMWF group showed significantly suppressed tumor growth. The LMWF and HMWF groups showed significantly increased survival times compared with that observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 31 publications
0
50
0
1
Order By: Relevance
“…These data suggest that the MyD88 signaling pathway may be downstream of SR-A and TLR-2 in this event. Moreover, recent studies have shown that the MyD88 signaling pathway is essential for SR-A ligand-induced antitumor effects in mouse NK cells (47) and for migration of human and mouse monocytes/macrophages (48). To address this hypothesis, we will characterize the downstream cascades of SR-A and TLR-2 signaling pathways in human BDCA1 ϩ mDCs stimulated by S. aureus, including the MyD88 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the MyD88 signaling pathway may be downstream of SR-A and TLR-2 in this event. Moreover, recent studies have shown that the MyD88 signaling pathway is essential for SR-A ligand-induced antitumor effects in mouse NK cells (47) and for migration of human and mouse monocytes/macrophages (48). To address this hypothesis, we will characterize the downstream cascades of SR-A and TLR-2 signaling pathways in human BDCA1 ϩ mDCs stimulated by S. aureus, including the MyD88 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Azuma et al suggested that, regardless of molecular weight (lower-molecular-weight fucoidan (LMWF: 6.6–40 kDa), intermediate-molecular-weight fucoidan (IMWF: 110–138 kDa), and high-molecular-weight fucoidan (HMWF: 300–330 kDa)), fucoidan-containing diet increases the survival time of mice [30]. Still, Matsubara et al argue that the pharmacological effects of fucoidan vary with molecular weight [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fucoidan has been shown to display immune-stimulating effects on dendritic (DC) cells [460][461][462][463] and natural killer (NK) cells [412,464]. Thus, fucoidan can enhance anticancer immunity through immune cell activation and influx and stimulation of the production of anticancer cytokines [10,421].…”
Section: Anticancer Activity Of Fucoidanmentioning
confidence: 99%